2019
DOI: 10.1186/s43044-019-0014-2
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) as independent predictors of outcome in infective endocarditis (IE)

Abstract: Background Early and accurate risk assessment is an important clinical demand in patients with infective endocarditis (IE). The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are independent predictors of prognosis in many infectious and cardiovascular diseases. Very limited studies have been conducted to evaluate the prognostic role of these markers in IE. Results We analyzed clinical, laboratory, and ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 36 publications
(33 reference statements)
0
26
0
Order By: Relevance
“… NLR > 3.045 for predicting EE: sensitivity 73.3%, specificity 51.9%, area under the curve 0.611, 95% CI 0.516–0.707; p = .028 26 …”
Section: Predictors For Eementioning
confidence: 99%
See 1 more Smart Citation
“… NLR > 3.045 for predicting EE: sensitivity 73.3%, specificity 51.9%, area under the curve 0.611, 95% CI 0.516–0.707; p = .028 26 …”
Section: Predictors For Eementioning
confidence: 99%
“…The NLR can be obtained immediately from a complete blood count. A retrospective study reported that an NLR above 3.045 measured on admission, exhibited a 73.3% sensitivity and a 51.9% specificity for predicting embolization 26 . Neutrophils and lymphocytes are of considerable importance in the inflammatory reaction associated with infection.…”
Section: Predictors For Eementioning
confidence: 99%
“…Up to now, several studies have investigated the relationship between admission NLR and IE [ 10 , 12 , 25 , 26 ]. Turak et al showed that NLR was associated with in-hospital mortality and central nervous system events in IE patients [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bozbay et al also investigated 171 IE patients and found that patients in the high NLR group had a higher incidence of in-hospital mortality, while NLR cannot be a useful prognostic marker during long-term follow-up [ 25 ]. Meshaal et al found that a higher NLR, TLC, neutrophil percentage, creatinine level, and CRP level upon admission were associated with increased in-hospital mortality and morbidity in IE patients [ 26 ]. We also evaluate the role of NLR and clinical outcome of IE patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation